Cardiopulmonary Bypass Ischemic Hepatitis Reported in Five Patients - Damasceno,Telma A. (2016)
Abstract Objective: In cardiac surgery, the lung, renal and neurological events are the most frequent complications. Less common, acute liver failure is a serious complication that adds high morbidity, mortality, and costs. Therefore, this communication aimed to retrospectively evaluate five patients who presented, in 2014, severe acute liver failure in the immediate postoperative period. Methods: Retrospective data analysis of patients' medical records that showed severe liver failure has been computed in the medical records of five patients undergoing cardiac surgery at the Hospital da Faculdade de Medicina de Ribeirão Preto – USP in the immediate postoperative period from February 1, 2014 to December 12, 2014. The study selected five males patients, 60 to 67 years old, cardiopulmonary bypass mean time of 101.4 minutes (varying from 80 to 140 minutes), who presented acute perioperative liver failure. Results: The five patients showed an impressive increase of blood transaminase (serum alanine aminotransferase), suggesting acute hepatitis. The evolution of all patients was catastrophic, with severe hemodynamic effects and death. Many studies suggest that systemic hypotension is an important pathogenic factor for ischemic hepatitis. However, our data and previous studies raise the possibility that other yet unknown factors other than hypotension may be part of the pathophysiology of cardiopulmonary bypass after ischemic hepatitis (anticoagulation inadequate for the quality of heparin and protamine, etc.). Conclusion: Currently, there are no conclusive studies on the prevention of perioperative liver failure. More well-designed studies are needed on the introduction and evolution of liver dysfunction after cardiac surgery.